Bilateral Renal Mass-Renal Disorder: Tuberculosis. (15th September 2013) - Tiryaki, Ozlem; Usalan, Celalettin; Alkan, Samet
Abstract : A 30-year-old woman has presented complaining of weakness and fatigue to her primary care physician. The renal sonography is a routine step in the evaluation of new onset renal failure. When the renal masses have been discovered by sonography in this setting, the functional imaging may be critical. We reported a case about bilateral renal masses in a young female patient with tuberculosis and renal insufficiency. Magnetic resonance (MR) has revealed the bilateral renal masses in patient, and this patient has been referred to our hospital for further management. The patient's past medical and surgical history was unremarkable.